BASIC LIFETIME MODEL FOR REENTRY TIME PREDICTION OF ARTIFICIAL SPACE OBJECTS - Abdul Rachman; Rhorom Priyatikanto (Jurnal Sains Dirgantara, 2018)
The identification of space debris and the prediction of its orbital lifetime are two important things in the initial mitigation processes of threat from falling debris. As a part of the development of related decision support system, this study focuses on developing a basic lifetime model of artificial space object based on a well-known theory and prediction scheme in the field of satellite reentry research. Current implemented model has not accounted atmospheric oblateness or other correcting factors, but it has a reasonably good performance in predicting reentry time of several objects with various initial eccentricities. Among 30 predictions conducted to 10 objects that reentered the atmosphere from 1970 to 2012, there are 13 calculations that yield prediction time with accuracy of < 30% relative to the actual reentry time. In addition, 11 calculations yields prediction time which were more accurate compared to the outputs from SatEvo software that is currently used in the decision support system on the falling debris operated by Space Science Center LAPAN. These results were considered satisfying and can be developed further by adopting the updated atmospheric model and by calculating other relevant correcting factors.